A geomorphic classification of ephemeral streams in arid regions - Sutfin, Nicholas A., author; Wohl, Ellen, advisor; Bledsoe, Brian, committee member; Kampf, Stephanie, committee member (Colorado State University. Libraries, 2013)
Current stream classifications do not adequately describe ephemeral streams in arid regions because these environments are characterized by high spatial and temporal variability of complex hydrologic interactions. To investigate the influence of channel form on riparian vegetation in the arid southwestern United States, I test a geomorphic classification for ephemeral streams based on the degree of confinement and the composition of confining material. I present five stream types: 1) bedrock channels entirely confined by exposed bedrock and void of persistent alluvium; 2) bedrock with alluvium channels at least partially confined by bedrock but containing enough alluvium to create bedforms that persist through time; 3) incised alluvium channels bound only by unconsolidated alluvial material into which they are incised; 4) braided washes that exhibit multi-thread, braided characteristics regardless of the degree and composition of confining material; and 5) piedmont headwater 0-2nd order streams confined only by unconsolidated alluvium and which initiate as secondary channels on piedmont surfaces. The objectives of this thesis were to i) validate distinct differences of channel geometry among the five stream types and ii) examine localized differences in geometry of the five stream types across watersheds with varying characteristics. Eighty-six study reaches were surveyed on the U.S. Yuma Army Proving Ground (YPG) and eighteen study reaches on Barry Goldwater Air Force Range (BMGR) in southwestern Arizona. Non-parametric permutational multivariate analysis of variance (PERMANOVA) for all 101 study reaches indicates significant differences (P<0.001) in channel geometry between the five stream types with regard to width-to-depth ratio, stream gradient, shear stress, and unit stream power. PERMANOVA results indicate no significant differences in channel geometry of individual stream types within watersheds of differing characteristics. A linear discriminant function of the four physical driving variables derived from 86 study reaches at YPG predict stream type with a 73% external hit rate for the 15 study reaches at BMGR. Classification and regression tree (CART) analysis identify thresholds for distinguishing stream types and indicates the relative importance of variables such that: width-to-depth ratio (W/D) correctly distinguishes 93.8% of braided channels (W/D > 91.2), shear stress (τ) correctly distinguishes 95.2% of bedrock channels (τ > 151.6 Pa), and unit stream power (ω) correctly distinguishes 68% of piedmont headwater channels (ω ≤ 35.63 W/m2). The resulting classification will provide a basis for examining relationships between channel characteristics, hydrologic process, riparian vegetation and ecosystem sensitivity of ephemeral streams in arid regions of the American Southwest.
Keywords: desert; stream classification; ephemeral channels; ecological sensitivity; braided channels; channel geometry